Micro-EDM drilling of tungsten carbide using microelectrode with high aspect ratio to improve MRR, EWR, and hole quality - Hourmand, M. (Elsevier Inc., 2016)
Miniaturized products currently have a lot of applications. This work comprehensively describes electrical discharge machining (EDM) and micro-EDM and compares the types of pulse generators, electrodes and methods for calculating material removal rate (MRR), electrode wear ratio (EWR), overcut and surface roughness for these methods. Various fabrication processes of micro-electrodes are explained as well. Moreover, in this research, experiments were performed with EDM machines to produce through micro-holes in WC-16%Co using a CuW microelectrode that was fabricated on the EDM machine. Fractional factorial design was used to analyze the effects of micro-EDM parameters (voltage, current, pulse-ON time, pulse-OFF time) on the MRR, EWR surface roughness, micro-cracks, migration of material to the workpiece, and overcut. It was discovered that there is a direct relationship between micro-hole surface roughness, the burr-like recast layer at the top surface and material removal rate. The current and capacitor were found to be the most significant factors affecting MRR. Besides, the effect of pulse-ON time on EWR appeared more significant than other parameters. However, the effects of voltage, current, and capacitor seemed more significant than pulse-ON time on the amount of micro-cracks. Various machining conditions produced different amounts of overcut. C, O, and Al migrated to the recast layer at the wall of the micro-holes because aluminum powder was used in the oil-based dielectric. It can be concluded that EDM machines can be used for producing micro-holes.